2009
DOI: 10.1007/978-3-540-85070-0_25
|View full text |Cite
|
Sign up to set email alerts
|

Application of CFD to Rail Car and Locomotive Aerodynamics

Abstract: CFD methods have been employed to solve a number of efficiency, safety and operational problems related to the aerodynamics of rail cars and locomotives. This paper reviews three case studies: 1) numerical models were employed to quantify the drag characteristics of two external railcar features; namely, well car side-posts and inter-platform gaps. The effects of various design modifications on train resistance and fuel usage were evaluated. 2) An operational safety issue facing railroad operators is wind-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It was found that two inter-car gaps with a 1/20th scale length of 25 mm increased the drag coefficient by 0.013. James et al 6 investigated the aerodynamic performances of an intermodal freight train with containers. The effects of inter-container spacing on the drag force were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that two inter-car gaps with a 1/20th scale length of 25 mm increased the drag coefficient by 0.013. James et al 6 investigated the aerodynamic performances of an intermodal freight train with containers. The effects of inter-container spacing on the drag force were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In calculus aerodynamic calculations, the one playing the most roles is the part of the frontal coefficient. Fuel consumption calculations are performed to determine the effect of reducing drag on locomotive fuel consumption (James C. Paul et al, 2009).…”
Section: Energy On Trainmentioning
confidence: 99%
“…Fuel requirements, of course, also depend very much on train speed and train weight. Assuming a constant train speed, the formulation of train requirements, according to Paul & Johnson (2009), is as follows: The shape of high-speed trains' nose is an important control factor that affects not only aerodynamic performance, but also aerodynamic noise (Y. An et al, 2017).…”
Section: Energy On Trainmentioning
confidence: 99%
“…In line with industrial needs a number of studies have analysed drag effects of open top wagons (Golovanevskiy et al, 2012), container wagons Flynn et al, 2013;Östh and Krajnović, 2013) and locomotives (Paul et al, 2009). Large differences in flow development and drag coefficients were observed between a single wagon and a series of wagons within a train consist (Östh and Krajnović, 2013).…”
Section: Freight Researchmentioning
confidence: 99%